К методике изучения динамики численности и плотности популяций насекомых, летящих на ультрафиолетовое излучение - Приставко, В.П. (Вестник зоологии, 1969)
The main methods and rules are described for expedition of black light traps when studying the dynamics of population quantity and density and migrations of insects flying to ultra-violet radiation.